2001
DOI: 10.1136/jcp.54.10.809
|View full text |Cite
|
Sign up to set email alerts
|

The use of a standard proforma in breast cancer reporting

Abstract: The introduction of a standard proforma led to a significant improvement in the completeness of breast cancer histopathology reports in this centre, but continued vigilance is needed to ensure that standards continue to improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Some studies have already revealed deficiencies in pathology laboratory reporting, notably on colorectal or breast cancers [23][24][25]. Other authors have already emphasized the value of synoptic or proforma pathology reports in colon cancer, breast cancer and melanoma [26][27][28][29]. We emphasize the need for a standardized report format or a checklist format (featuring a list of features of agreed importance) for hilar cholangiocarcinoma [2].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have already revealed deficiencies in pathology laboratory reporting, notably on colorectal or breast cancers [23][24][25]. Other authors have already emphasized the value of synoptic or proforma pathology reports in colon cancer, breast cancer and melanoma [26][27][28][29]. We emphasize the need for a standardized report format or a checklist format (featuring a list of features of agreed importance) for hilar cholangiocarcinoma [2].…”
Section: Discussionmentioning
confidence: 99%
“…This practice has improved the percentage of prognostic information contained in pathology reports. [1][2][3][4][5][6] There are no such standardized pathology reports in use in head and neck cancer in Victoria.…”
mentioning
confidence: 99%
“…A structured proforma report ensures clarity and produces consistency of written communication whilst acting as an aide memoire to the reporting pathologist [4,5]. The standard for the audit was not met in that of the 386 reports examined only 115 (30%) had all the expected data items.…”
Section: Discussionmentioning
confidence: 99%